The influence of percentage of shade on the growth of Mucuna bracteata D.C. seedling origin cuttings with different IAA concentration. - rizki fauzi; Meiriani Meiriani; Asil Barus (Jurnal Agroekoteknologi, 2016)
The influence of percentage of shade on the growth of Mucuna bracteata D.C. seedling origin cuttings with different IAA concentration. The research was conducted in Desa Sendang Rejo, Kecamatan Binjai, Kabupaten Langkat with altitude ± 50 m above the sea level from Juni to September 2015. This research used factorial split plot design with 2 factors. The first factor was Intensity of Shade  ( 0 %, 25 %, 50 %, 75 % ) and the second factors was IAA concentration ( 0 ppm, 100 ppm, 200 ppm ) with 3 replication. The result of the research showed that mucuna seed growth were significantly effect to without shade (0 %) than with application if shade. Application of IAA PGR 200 ppm were significantly effect to increased mucuna growth in 8 week after planting. The best treatment of the research were without shade 0 % (N0) with application of IAA 200 ppm (N0A2).